ANALISIS REINKARNASI DALAM FILM A DOGâ€™S PURPOSE YANG DISUTRADARAI OLEH LASSE HALLSTROM - Polakitan, Iriani Fritza Kurnia; Sigarlaki, Stephani J.; Manus, Jeane Angela (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTThis research is entitled â€œAnalisis Reinkarnasi dalam Film A Dogâ€™s Purpose yang Disutradarai oleh Lasse Hallstromâ€. It is written to fulfill the requirement of accomplishing bachelor degree in English Department Faculty of Humanities Sam Ratulangi University. The focus of this research is about the reincarnation delineated and the impact of reincarnation towards the character in the Film A Dogâ€™s Purpose. This research includes the concept of reincarnation, film analysis, and character analysis. The writer used two theories, such as the theory of film analysis by Klarer in his book â€œAn Introduction to Literary Studiesâ€ (2005) and the theory of character analysis written by Stanton in his book â€œIntroduction to Fictionâ€ (1965) to identify, describe and analyze the data. The result of this research shows that there are four reincarnations that occurred in this film, such as first reincarnation, second reincarnation, third reincarnation, and forth reincarnation. Each reincarnations has several unique impacts of reincarnation towards other characters in the film.Keywords: Reincarnation, Character, Film, A Dogâ€™s Purpose, Dog, Impact